HUBUNGAN MOTIVASI, PERSEPSI, DAN PENGETAHUAN IBU PADA MASA KEHAMILAN DAN PEMBERIAN AIR SUSU IBU - Nurhasmadiar Nandini (Fakultas Kesehatan Universitas Nahdlatul Ulama Surabaya, 2018)
In Indonesia, the coverage of infants that get breastfeeding exclusively were still low. In 2013, the average coverage of exclusive breastfeeding in Indonesia was 54,3%. Surabaya, in East Java Province, is one of the city with low coverage of exclusive breastfeeding. The average of babies who got exclusively breastfeeding in Surabaya since 2012 2015 were 63,13%, still below the target of Health Ministry. This research conducted to analyze the relationship between motivation, perception, and knowledge of pregnant women and breastfeeding practice. The respondent of the research was pregnant woman and the study continued until they are giving birth. Sample size was 79 mothers in East Surabaya. Result showed that majority mothers have high motivation to breastfeed, positive perception related to breast milk, low knowledge about breastfeeding, and they already give breastmilk only for their babies during the first week. Conclusion was there was no significant relationship between motivation, perception, and knowledge towards breastfeeding practice. This is caused by there were a lot of factors that influenced directly or indirectly towards mothers decisionand practice to breasfeed or not.